2005
DOI: 10.1073/pnas.0502762102
|View full text |Cite
|
Sign up to set email alerts
|

Distinct basal ganglia territories are engaged in early and advanced motor sequence learning

Abstract: In this study, we used functional MRI (fMRI) at high field (3T) to track the time course of activation in the entire basal ganglia circuitry, as well as other motor-related structures, during the explicit learning of a sequence of finger movements over a month of training. Fourteen right-handed healthy volunteers had to practice 15 min daily a sequence of eight moves using the left hand. MRI sessions were performed on days 1, 14 and 28. In both putamen, activation decreased with practice in rostrodorsal (assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
467
6
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(543 citation statements)
references
References 50 publications
61
467
6
9
Order By: Relevance
“…Imaging studies show changes in the activation of the dorsal striatum (Lehericy et al 2005) and electrophysiological experiments in animals show evidence for reorganization of corticostriatal circuits during early stages of motor skill learning (Brasted and Wise 2004;Costa et al 2004, Yin et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging studies show changes in the activation of the dorsal striatum (Lehericy et al 2005) and electrophysiological experiments in animals show evidence for reorganization of corticostriatal circuits during early stages of motor skill learning (Brasted and Wise 2004;Costa et al 2004, Yin et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The sensorimotor cortex interacts with the basal ganglia (Pisani et al 2005;Costa 2007), the cerebellum and other sensory as well as associative cortical areas . Imaging studies in humans demonstrate activation of the striatum during skill learning (Seitz et al 1990; Lehericy et al 2005;Wachter et al 2009). These studies also suggest that striatal circuits undergo plastic modifications as neuronal activation shifts from the associative, rostrodorsal region to the sensorimotor, caudoventral region of the putamen (Lehericy et al 2005) in association with learning a new finger tapping sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies, additionally, have reported enhanced post-learning subcortical processing (Doyon et al, 2009;Lehericy et al, 2005;Van Turennout et al, 2003), although the results are rather mixed (see Ashby et al, 2010 for a detailed discussion). To examine changes in cortical and subcortical activity over time, we divided our experiment into four different sets (120 trials/set, 2 sets/phase), each consisting of a complete set of unique stimulus combinations, and conducted an additional GLM analysis.…”
Section: Ruling Out Practice Effectsmentioning
confidence: 99%
“…also raised by McGuire et al (1991). The anterior portion of the striatum, connected with prefrontal and premotor structures, is activated bilaterally during the acquisition of unilateral motor tasks, while the posterior part, involved in sensorimotor functions, is activated at advanced stages of learning (Lehéricy et al 2005). The learning and execution of movements might require the temporal coordination, with minimal delays between the hemispheres that the bilateral projection affords.…”
Section: Bda Tracingmentioning
confidence: 99%